The Effect of Keeler’s Strategy on Cognitive Achievement and Learning Offensive Skills in Volleyball - Alia Hussein Obaid; Ahmed Hussein Jiyad; Alaa Kazem Armout (Institute of Medico-legal Publications Pvt Ltd, 2021)
Excellence in the sports field has become one of the essential metrics on which the progress of nationsand peoples is viewed. In order to draw up valid scientific policies represented in the use of modernstrategies and methods to prepare the appropriate educational and training curricula in order to reachthe learners to the highest levels, individual learning strategies must be used, which is self-learning asthey take into account the individual differences between the learners and reduce the time and effortrequired for this process. Keller’s strategy is for individual or personal learning. One of the strategiesthat achieve this goal.The researchers believe that learning with the Keeler strategy is a personal process, as learning cannotbe given or indoctrinated but must result from the educated person’s experience and ability to retrievehis memory to perform better than what he witnessed. The field of physical education and education.The researchers identified the research community with students of the second stage in the College ofPhysical Education and Sports Sciences - the University of Kufa for the academic year 2017-2018,numbering 30 students, divided into two groups, each group consisting of (12) students, one of whomwas chosen randomly to represent the experimental group to which the educational program willbe applied. Under consideration is what will be applied to the other, which is the control group, theprescribed curriculum, and according to the method used, and the seven female students were chosento represent the sample that will be conducted on the exploratory experiment.